The Perception of Totalitarianism and Authoritarianism in Various Universitas Andalas Students: A Reader-Response Criticism of George Orwell's Nineteen Eighty-Four - Amanda Aisyah; Edria Sandika (Linguistika Kultura, 2021)
This research studies the readers' responses to George Orwell's Nineteen Eighty-Four regarding their perception of totalitarianism and authoritarianism in various Universitas Andalas students as based on the said novel. This research focuses on how the novel's readers understand totalitarianism and authoritarianism after reading Nineteen Eighty-Four. Furthermore, this research also investigates the readers' answer on why they relate those mentioned concepts to their lives based on the novel Nineteen Eighty-Four. In analyzing the readers' responses, we apply a reader-response theory that focuses solely on the object's extrinsic elements, that is, in this case, the readers. As for the study method, we utilize the quantitative mixed with the qualitative method and library research.